Evaluasi Perilaku dan Viskositas Material Pasir Kelanauan pada Kondisi Terlikuifaksi dengan Menggunakan Piezocone - Johan, Albert; Rahardjo, Paulus Pramono; Widjaja, Budijanto (Jurnal Teknik Sipil, 2024)
Abstract Liquefaction is phenomenon of the loss of shear strength of saturated sandy soil. Liquefaction has become one of the primary concerns for Indonesia and the world, especially after the occurrence of liquefaction in Palu due to Palu-Donggala earthquake. Learning from the liquefaction phenomena after the Palu-Donggala earthquake event on 28 September 2018, many researchers have conducted liquefaction and flow slide study. In order to complete the study of the liquefaction phenomenon, an experimental study using shake table, chamber, and piezocone is conducted to evaluate the behaviour and viscosity of liquefied silty sand material. Based on the observation during liquefied condition, the silty sand material will experience an increase in excess pore pressure and a decrease in tip resistance. In addition, it is also known that sleeve resistance, speed of penetration of the piezocone, and zone of influence due to piezocone penetration are the main keys in determining the viscosity of the silty sand material during liquefied condition Keywords: Liquefaction, viscosity, silty sand, piezocone